Detection and localization of breaks in railroad tracks using time domain reflectometry - Diehl, Nathaniel P. (My University, 2025)
A new technique is proposed for detecting and locating breaks in railroad tracks using time domain reflectometry that provides real time measurement of the track condition while requiring minimal additions to existing railroad hardware. Time domain reflectometry is a technique that measures reflection delay of electrical pulses to determine the location of impedance changes. The feasibility of the technique is evaluated using an experimental setup with a real-world railroad track as well as a digital twin model. The experimental platform includes equipment designed to transmit and detect signals along the rail, which are used to measure the reflection delay of signals on a real-world railroad track. The simulation done with a digital twin observes the change in reflection delay caused by a break in the rail. Monte Carlo simulation is used to augment the observations from the digital twin by adding random noise. These noisy observations are used to assess the effectiveness of the break detection and break location estimation methods. Results demonstrate that time domain reflectometry is a viable approach for detecting and locating breaks in railroad tracks. Future work could analyze this technique under a nonconstant propagation velocity and on a wider range of defect types.
Keywords: Railroad track break detection locating reflectometry; Time domain reflectometry